2015
DOI: 10.1016/j.juro.2015.01.090
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Expression of Structural, Barrier and Differentiation Related Proteins, and Chondroitin Sulfate in Feline and Human Interstitial Cystitis

Abstract: Purpose The urothelium of cats diagnosed with feline interstitial cystitis (FIC) was analyzed to determine if abnormalities in protein expression patterns could be detected, and whether the pattern of expression was similar to that observed in human Interstitial Cystitis/Bladder Pain Syndrome (IC) patients. The proteins that were analyzed are involved in cell adhesion, barrier function, comprise the glycosaminoglycan (GAG) layer, or are markers of differentiation. Methods Formalin-fixed biopsies from 8 cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Multiple studies tried to explain the pathogenesis of FIC in cats by using animal models (Logadottir et al, 2014;Dogishi et al, 2017) like mice and rats or even by comparing it with human interstitial cystitis (IC) (Hauser et al, 2015). In fact, some of these studies revealed a part of the pathophysiology of the syndrome, yet still investigating the disease condition in naturally-occurring model of IC in cats may permit more accurate results than those obtained by acute models of inflammation/injury of the bladder in healthy animals.…”
Section: Research Articlementioning
confidence: 99%
“…Multiple studies tried to explain the pathogenesis of FIC in cats by using animal models (Logadottir et al, 2014;Dogishi et al, 2017) like mice and rats or even by comparing it with human interstitial cystitis (IC) (Hauser et al, 2015). In fact, some of these studies revealed a part of the pathophysiology of the syndrome, yet still investigating the disease condition in naturally-occurring model of IC in cats may permit more accurate results than those obtained by acute models of inflammation/injury of the bladder in healthy animals.…”
Section: Research Articlementioning
confidence: 99%
“…Edema, inflammatory cells (e.g., lymphocytes, eosinophils, neutrophils), and disruptions of the mucosa, submucosa, and muscular tissue were recorded. Immunohistochemistry and immunofluorescence were performed as previously described (10,26). Controls included a known positive for each antibody, a negative control omitting the primary antibody, and for the ChABC-treated rat bladders the slide was not treated with ChABC to demonstrate the epitope was released by the in vivo treatment.…”
Section: Bladder Histopathology and Immunolabelingmentioning
confidence: 99%
“…There is a strong and growing body of evidence showing changes in the expression of TJ-associated proteins in biopsies from patients with IC/BPS (Slobodov et al, 2004; Hauser et al, 2008; Sanchez Freire et al, 2010; Lee and Lee, 2014; Hauser et al, 2015). TJs consist of a network of cytosolic and membrane proteins that associate to seal the paracellular space between adjacent epithelial cells just beneath their apical surface.…”
Section: Introductionmentioning
confidence: 99%